EFEKTIVITAS PIJAT WOOLWICH TERHADAP PRODUKSI ASI POST PARTUM DI PUSKESMAS PAYUNG SEKAKI PEKANBARU - Sukriana Sukriana; Yulia Irvani Dewi; Sri Utami (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
An important cause of breastfeeding failure is perceptions among mothers that they were not producing enough breast milk to meet the nutritional needs of infants, which affected on oxytocin release. It can be solved by doing Woolwich massage as pleasant forms of touch, gently stimulating the nipple can leads to oxytocin secretion. The purpose of this research is to know the influence of Woolwich message against breast milk production at working area of Payung Sekaki Health Center. Using quasi-experimental study designs with pre-post test intervention, a number of 34 normal postpartum mothers were regarded as the control group. The measuring instruments used were Mabaki breast pump and observation sheets. Applying univariate analysis to determine the frequency distribution of respondent characteristic. Meanwhile, bivariate analysis with t-dependent and t-independent test showed that there were differences in the breast milk production average between experiment group and control group. The outcomes were 80.92ml breast milk from experiment group (after given the treatment) and only 66.82ml breast milk from control group with p value = 0.000 <α (0.05). This investigation indicated that Woolwich massages effectively increase breast milk production during postpartum phase. Mothers are advised to utilize Woolwich massages as one of the methods to intensify breast milk production.Keywords : Breastmilk Production, Woolwich Massage, Postpartum